A case report of primary meningococcal pericarditis secondary to Neisseria meningitidis in a young female patient - Matthew Green; Peter Harrison; Anshuman Sengupta; Dominik Schlosshan (IDCases, 2022)
Pericarditis is responsible for approximately 5 % of emergency admissions due to chest pain. Pericarditis secondary to Neisseria meningitidis (meningococci) was originally reported in 1918, and remains a rare diagnosis. We report a case of primary meningococcal pericarditis presenting with non-specific symptoms, illustrating the importance of considering rarer causes of pericardial effusion. A previously fit and well 23-year-old female presented to her local hospital with a 2-day history of feeling generally unwell with myalgia and fevers and was initially discharged. Four days following discharge the patient re-presented with worsening symptoms. A Computed Tomography Pulmonary Angiogram (CTPA) demonstrated a large pericardial effusion with subsequent bedside echocardiogram confirming a global pericardial effusion of up to 3 cm. This required drainage, with blood cultures and pericardial fluid showing polymerase chain reaction positivity for Neisseria meningitidis, serogroup B. Our report describes a rare case of Primary Meningococcal Pericarditis secondary to serotype B meningococcal infection. The European Society of Cardiology propose criteria that warrant hospital admission and an aetiology search for certain patients with pericardial disease. These criteria provide a useful framework to help select those minority of patients in whom a more serious underlying cause is present. Blood cultures provide vital information to allow us to complete a thorough aetiological search and empirical antibiotics can cloud the clinical picture, making it harder to identify causative organisms. To aid the early administration of appropriate therapy, it may be pertinent to recommend a low threshold for taking blood cultures in patients with pyrexia and pericarditis or pericardial effusion.